Chirp-pulsed eddy current testing for crack detection in low-carbon steel - Le, Dang-Khanh; Phuong Hoang, Sy; Minh Le, Duc; Huy Pham, Phuong; Hieu Trieu, Trung; Le, Minhhuy (International Journal of Reconfigurable and Embedded Systems (IJRES), 2025)
This paper introduces a signal processing feature for chirp-pulsed eddy current testing (C-PECT) to improve crack detection in low-carbon steel, a common material in maritime structures. While C-PECT is an established technique, inspecting ferromagnetic materials is challenging due to significant background noise from lift-off variations and material permeability. The novelty of this work lies in the proposal of a frequency-domain integration feature designed to suppress this noise. The method utilizes a chirp-pulse-excited probe with a Hall sensor to measure the magnetic field response. By integrating the signal's magnitude spectrum, the frequency feature effectively flattens the background and enhances the signal-to-noise ratio. Experimental validation on a low-carbon steel specimen with artificial cracks demonstrates the feature's superior performance in providing clear, high-contrast crack indications compared to a conventional time-domain analysis. The results indicate that this approach offers a simple, computationally efficient, and robust solution for the qualitative detection and localization of cracks, enhancing structural integrity assessments in noisy industrial environments.